Mediatisasi Hadis: Transformasi Interpretasi dalam Era Digital - Nahied, Muhammad Afda; Ubaidillah, Rofiatul (UIN Kiai Haji Achmad Siddiq Jember, 2024)
Social media is not only a space for entertainment for entertainment activists but also a space for freedom of expression and freedom to argue and convey a message, especially in the context of hadith studies. This research will present the transformation of hadith interpretation in the digital era. The method used is a type of literature; data is obtained through research in books, articles, and journals and then analyzed using a mediatization approach. This research shows that social media has become the central platform for disseminating, interpreting, and understanding hadith in modern society. This phenomenon reflects a shift in how society accesses and interacts with religious information, with social media becoming an effective channel for disseminating religious messages, including hadith.